Gamelan Notation Reading Training for Elementary School Students at SDN Kedunglosari, Tembelang, Jombang - Wahyudi, Wahyudi; Sari, Ayu Titis Rukmana; Sahari, Sutrisno; Mukmin, Bagus Amirul; Zaman, Wahid Ibnu; Hunaifi, Abdul Aziz; Aka, Kukuh Andri; Mahardika, Ronny (Dimar : Jurnal Pengabdian Masyarakat, 2025)
Training in reading gamelan notation for elementary school students is a strategic effort to introduce and nurture traditional musical literacy from an early age. This activity was carried out at SDN Kedunglosari, Tembelang District, Jombang, for two days involving 35 fourth and fifth grade students. The main objective was to provide basic understanding of the numerical symbols (1–7) in Javanese gamelan notation and to improve students' ability to read and perform gamelan notation collaboratively. The methods used included demonstrative and participatory approaches through hands-on practice, tone-based educational games, and visual media. The results showed that 91.4% of students actively participated, with average satisfaction and understanding scores in the "very good" category. Beyond enhancing musical literacy, the program also strengthened student collaboration, concentration, and appreciation of local cultural values. This initiative is expected to serve as a foundational model for culture-based art education at the primary level and be replicable in other schools.